Cover Image. (27th January 2022) - Maasri, Alain; Jähnig, Sonja C.; Adamescu, Mihai C.; Adrian, Rita; Baigun, Claudio; Baird, Donald J.; Batista‐Morales, Angelica; Bonada, Núria; Brown, Lee E.; Cai, Qinghua; Campos‐Silva, Joao V.; Clausnitzer, Viola; et al.
Abstract : The cover image is based on the Viewpoint A global agenda for advancing freshwater biodiversity research by Alain Maasri et al., https://doi.org/10.1111/ele.13931 . Image Credit: Solvin Zankl.